IMPLEMENTASI FUNGSI MANAJEMEN DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH DASAR - Ulyani, Aap Siti; Zohriah, Anis (Jurnal Manajemen Pendidikan, 2023)
Educational management is a necessary tool to achieve educational goals. The application of management principles in the field of education is an element of internal management education. Planning, organizing, directing, and controlling activities in the field of education are part of education management. The management function is a fundamental part of every activity and will always be part of the management process. Internal managers will use it as a reference in carrying out activities to achieve goals. The management function is a fundamental component that will always exist and be ingrained in the management process. These functions will serve as a guide for managers as they carry out activities to achieve goals. In the 20th century, a French industrialist named Henry Fayol was the first to introduce management functions. The management function has not been fully implemented in educational institutions as a whole, errors or deficiencies often occur in educational institutions. Consequently, educational institutions must implement management functions to improve their quality. This is so that educational institutions can provide quality teaching and learning rights. Therefore understanding the implementation of educational management functions is necessary. Seven management functions, (Rahman, 2020), namely: Planning, Organizing, Staffing, Directing, Coordinating, Reporting.